Praktyczne problemy zajęcia wierzytelności z rachunku bankowego w administracyjnym postępowaniu egzekucyjnym - Majczak, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The aim of this MA thesis is to present the most commonly chosen mean of execution of monetary obligations — execution against bank accounts. The study discusses a concept of a bank account, its essence and legal regulation, as well as describes the legal basis of execution against bank accounts. The article analyses enforcement proceedings, legal consequences of the attachment of the debtor’s bank account, limitations of execution. In this article, the formal-dogmatic method of working on the issue of enforcing a bank account. The analysis includes questionable issues within both the theoretical and practical field as well as recent doctrinal and judicial achievements. The thesis refers to the legal regulation currently in effect in the scope of the study and indicates adopted amendments which will come into force on 19 February 2021.
Keywords: bank account; the subject of enforcement; execution of the bank account; discontinuanceof the proceedings; delivery